An Unknown Type of Minbar and Its Historical Significance - Schacht, Joseph (Ars Orientalis, 1957)
Keywords: Ghuraba, mosquée al- (Houmt Souk, Djerba); Monuments -- Djerba

Notes mozabites - Schacht, Joseph (Al-Andalus, 1957)
On Ibāḍī mosques in Ouargla, Mīzāb and at Jerba (with plans and photographs), on Ibāḍī cemeteries in Mīzāb, on style in Ibāḍī architecture, and finally some observations on “modernism and the movement of sheikh Ibr. Bayyūḍ” and on education in Mīzāb.
Keywords: Architecture -- Mzab; Ghuraba, mosquée al- (Houmt Souk, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Monuments -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba)